2015
DOI: 10.1002/rcs.1646
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a flapless protocol for computer‐guided zygomatic implant placement in human cadavers: expectations and reality

Abstract: Computer-guided minimally-invasive flapless zygomatic implant surgery remains challenging. Careful planning and perfect stability of the surgical guide are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Vrielinck et al inserted 18 ZIs using customized surgical template and found mean entry, exit, and angle deviations were 2.77 mm, 4.46 mm, and 5.1 degrees, respectively (Vrielinck et al, 2003 ). Schiroli et al and Vosselman et al also designed and fabricated surgical template specific for ZI surgery and gained high accuracy in ZI placement (Schiroli et al, 2016 ; Vosselman et al, 2021 ). Seldom study reported the accuracy in freehand ZI surgery, Gao et al applied digital ZI planning but conducted ZI surgery by freehand, the entry, exit, and angle deviations of 14 ZIs were 4.99 ± 2.66 mm, 6.11 ± 4.28 mm and 8.36 ± 5.3 degrees, respectively (Xing Gao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vrielinck et al inserted 18 ZIs using customized surgical template and found mean entry, exit, and angle deviations were 2.77 mm, 4.46 mm, and 5.1 degrees, respectively (Vrielinck et al, 2003 ). Schiroli et al and Vosselman et al also designed and fabricated surgical template specific for ZI surgery and gained high accuracy in ZI placement (Schiroli et al, 2016 ; Vosselman et al, 2021 ). Seldom study reported the accuracy in freehand ZI surgery, Gao et al applied digital ZI planning but conducted ZI surgery by freehand, the entry, exit, and angle deviations of 14 ZIs were 4.99 ± 2.66 mm, 6.11 ± 4.28 mm and 8.36 ± 5.3 degrees, respectively (Xing Gao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatments with conventional implants performed under surgical guides have achieved survival rates similar to conventional procedures [ 22 ], providing greater accuracy and precision than freehand techniques [ 23 ]. On the other hand, due to variations in the position and angulation of implants with respect to the previous computer-assisted planification zygomatic implants, surgical guides have demonstrated to be highly imprecise [ 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, CAD-CAM technology [26] has helped in the development of minimally invasive surgical techniques guided by intraoral splints [27] or computerassisted procedures [28][29][30]. Treatments with conventional implants performed under surgical guides have achieved survival rates similar to conventional procedures [31], providing greater accuracy and precision than previous techniques [32,33].…”
Section: Introductionmentioning
confidence: 99%